Precious Metals and Oil Price Dynamics - Abdulrazak Nur Mohamed; Idiris Sid Ali Mohamed (International Journal of Energy Economics and Policy, 2023)
The aim of this study is to examine dynamic relationship among the prices of four precious metals (gold, silver, platinum, and palladium), oil price, and the US dollar/euro exchange rate. Recent literature for precious metals (gold, silver, platinum, palladium) and oil depict a lot contradiction results of their nexus in the long and short runs. So that, there is still much to investigate and learn about their relationship between them and with the exchange rate. The monthly data span from January 1990 to October 2021 is utilized, the study applies the co-integration analysis, multivariate Granger causality test and Variance Decomposition (VDC) analysis. The result shows the evidence of a long-run equilibrium relationship but weak feedbacks in the short run. The precious metal markets respond significantly (but temporarily) to a shock in any of the prices of the other metal prices and the exchange rate. Furthermore, we discover some evidence of market overreactions in the palladium and platinum cases as well as in the oil market. The study implies whether there are overreactions and re-adjustments or not, investors may diversify at least a portion of the risk away by investing in precious metals, oil, and the euro.